Academia and Higher Learning in Popular Culture
XII, 273 p.
Keywords: This edited volume focuses on the cultural production of knowledge in the academy as mediated or presented through film and television. This focus invites scrutiny of how the academy itself is viewed in popular culture from The Chair to Terry Pratchett's ‘Unseen University’ and Doctor Who's Time Lord Academy among others. Spanning a number of genres and key film and television series, the volume is also inherently interdisciplinary with perspectives from History, Cultural Studies, Gender Studies, STEM, and more. This collection brings together leading experts in different disciplines and from different national backgrounds. It emphasises that even at a point of mass, global participation in higher education, the academy is still largely mediated by popular culture and understood through the tropes perpetuated via a multimedia landscape. Dr Richard Scully, BA (Hons), PhD (Monash), FRHistS is Associate Professor in Modern History at theUniversity of New England, Australia. His research focuses on the history of cartoons, caricature, and graphic satire. He has co-edited four collections of essays, including two volumes on Australia’s migrant and minority press for Palgrave Macmillan. Professor Marcus Harmes is Associate Director Research at the University of Southern Queensland College, Australia, and teaches legal history in the law degree. He has published extensively in the fields of religious and political history, with a particular emphasis on British religious history and constitutional history.